Experimental and numerical investigations of high strength steel unlipped channel sections under interior-two-flange loading - Lan, Xiaoyi (2024)
This paper presents laboratory tests, numerical simulations and web crippling design of high strength steel unlipped channel sections under interior-two-flange loading. An experimental programme comprising 10 test specimens (with six for grade S690 high strength steel and four for grade S960 high strength steel) was firstly implemented, and test results including failure modes, full load-deformation curves and ultimate loads were reported. Subsequently, finite element models were constructed and validated against the obtained test results, and then used to conduct supplementary parametric studies to widen the examined parameter ranges of high strength steel unlipped channel sections. Considering that relevant codified design rules are absent, the applicability of the design rules of EN 1993–1-3, EN 1993–1-5 and AISI S100 for normal strength steel unlipped channel sections to their high strength steel counterparts was evaluated against the obtained test and numerical results. It is shown that the resistance predictions from the codified design provisions were generally inaccurate and scattered. Hence, a modified AISI S100 design method and a slenderness-based design method were proposed and demonstrated to be accurate, consistent and reliable for the web crippling design of high strength steel unlipped channel sections under interior-two-flange loading.